Development and Validation of Liquid Chromatography/Tandem Mass Spectrometry Analysis for Therapeutic Drug Monitoring of Risperidone and 9‐Hydroxyrisperidone in Pediatric Patients with Autism Spectrum Disorders. Issue 6 (26th June 2016) - Vanwong, Natchaya; Prommas, Santirat; Puangpetch, Apichaya; Hongkaew, Yaowaluck; Nuntamool, Nopadol; Nakorn, Chalitpol Na; Ngamsamut, Nattawat; Limsila, Penkhae; Sukasem, Chonlaphat
Abstract : Background: Risperidone (RIS) is a widely used atypical antipsychotic drug. We developed and validated a sensitive and accurate LC‐MS/MS method, which requires a small‐volume of plasma and small‐volume injection for measurement of RIS levels in ASD pediatric patients. We also investigated the relationship between RIS levels and RIS dosages, including prolactin levels. Method: Blood samples were processed by protein precipitation extraction. Only 1 μl of sample was injected. Plasma samples were separated on a C18 column (4.6 cm × 50 mm; 1.8 μm particle size). Detection was by MS‐MS with an analytical run time of 6 min. Results: The inter‐day accuracy of RIS was 101.33–107.68% and 95.24–103.67% for 9‐OH‐RIS. The inter‐day precision of RIS was ≤7.27% CV and ≤7.41% CV for 9‐OH‐RIS. The extraction recovery of RIS and 9‐OH‐RIS were 95.01 ± 7.31–112.62 ± 7.50% and 90.27 ± 11.15–114.00 ± 10.35%, respectively. This method was applied in the therapeutic drug monitoring of ASD pediatric patients. Higher RIS dosage has a tendency to produce higher RIS plasma levels. The high RIS plasma levels have a tendency to produce hyperprolactinemia. Conclusion: The determination of RIS in individual patients might be clinically useful for monitoring and prediction of treatment response.